Thermoelastic equation of state of boron subphosphide B₁₂P₂ - Solozhenko, V.L.; Cherednichenko, K.A.; Kurakevych, O.O. (Сверхтвердые материалы, 2017)
Compressibility of boron subphosphide B₁₂P₂ has been studied under quasi-hydrostatic conditions up to 26 GPa and 2600 K using laser-heated diamond anvil cell and angle-dispersive synchrotron X-ray diffraction.